2020
DOI: 10.1029/2020ja028463
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Solar Wind Structure on Nanodust Dynamics in the Inner Heliosphere

Abstract: Several interplanetary spacecraft have inferred the presence of nanometer-sized dust grains in the inner heliosphere accelerated to near-solar wind velocities based on observations by radio wave antennas. These "nanodust" grains exhibit unique behavior in interplanetary space as they are strongly affected by both the solar gravitational force and the electromagnetic Lorentz force from the convecting interplanetary magnetic field. Here, we study the dynamics of nanodust grains in the inner heliosphere via a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 116 publications
2
12
0
Order By: Relevance
“…We make this comparison with the full understanding that the response mechanism of the STEREO/WAVES instruments to high‐velocity nanodust grains is poorly understood and apparently different between STEREO A and B, likely due to their opposite attitude with respect to the nanodust grain fluxes (e.g., see Meyer‐Vernet, Lecacheux, et al., 2009). We also reiterate that per our previous study (Poppe & Lee, 2020), we found that the episodic nature of the observed single‐hits on STEREO A suggested a strong degree of variability in the initial production of nanodust grains themselves in the inner heliosphere, something we do not model here. Thus, this comparison primarily pertains to whether or not nanodust grain fluxes can access 1 au at a given point in time, not whether STEREO/WAVES will definitively experience nanodust grain impacts at such times.…”
Section: Model Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…We make this comparison with the full understanding that the response mechanism of the STEREO/WAVES instruments to high‐velocity nanodust grains is poorly understood and apparently different between STEREO A and B, likely due to their opposite attitude with respect to the nanodust grain fluxes (e.g., see Meyer‐Vernet, Lecacheux, et al., 2009). We also reiterate that per our previous study (Poppe & Lee, 2020), we found that the episodic nature of the observed single‐hits on STEREO A suggested a strong degree of variability in the initial production of nanodust grains themselves in the inner heliosphere, something we do not model here. Thus, this comparison primarily pertains to whether or not nanodust grain fluxes can access 1 au at a given point in time, not whether STEREO/WAVES will definitively experience nanodust grain impacts at such times.…”
Section: Model Resultssupporting
confidence: 83%
“…In addition to the magnitude of the HCS tilt, the sign of Denoted in colors (green, red, blue) are specific CRs for which we have modeled nanodust dynamics for our current study. For reference, our previous study (Poppe & Lee, 2020) (1936, 1956, 1976, 1996, 2016, 2036, 2056, and 2076) that straddle the defocusing-to-focusing transition that occurred near CR 1950. A similar defocusing-to-focusing transition is expected in the upcoming solar cycle 25, and thus, we use these eight CRs to model and predict the behavior of nanodust grains during solar cycle 25 in Section 3.3.…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…A sharp drop in temperature value (almost two times, in HCS region during periods of solar minimum) may be associated with the properties of plasma sources near the HCS, as well as, possibly, with the interaction of plasma flows with a rarefied dust component or with other possible factors not taken into account that require further investigation and interpretation (e.g., [65][66][67][68][69]).…”
Section: Comparison Of Numerical Results With the Observational Datamentioning
confidence: 99%